Business Agreements That Cause Unfair Business Competition - Ida Nadirah (International Journal Reglement & Society (IJRS), 2020)
In today's business world, there are actually many agreements that contain unfair elements against parties whose economic or social weaknesses are weaker on the pretext of maintaining unfair business competition. However, it cannot be denied that behind these business practices there are various kinds of competition. which is not healthy. This writing uses a normative juridical legal research method (normative research) with descriptive analytical research specifications that use secondary data. The data collection procedures are in the form of documentation of notes or quotations, searching legal literature, books and others related to problem identification both offline. and online which are then analyzed through the content analysis method (centent analysis method) with a focus on the problem of how the elements of a business agreement cause unfair business competition and how the responsibility of business actors to business agreements that cause unfair business competition. Whereas some elements of the agreement that cause unfair business competition are agreements to control the production and or marketing of goods and or services which may result in monopolistic practices and unfair business competition, an agreement that sets the price for a good and or service that must be paid by consumers or customers in the same relevant market.